Faith, Identity, and Ethnocentrism: A Case Study of Chinese Evangelical Churches in Germany - Ma, Tianji (Transformation, 2026)
This article explores the interplay of faith, identity, and ethnocentrism within Chinese evangelical churches in Germany, emphasizing the critical role of their unique diasporic context. While cultural and theological factors significantly shape these congregations, the study highlights the influence of internal mechanisms, including leadership structures, status dynamics, approaches to mission and service, and hermeneutical frameworks of Scripture and orthodoxy. These elements collectively foster an ethnocentric ethos that prioritizes internal cohesion but often limits engagement with the host society and other faith communities. In its concluding reflections, the study offers some insights to address these challenges, advocating for a more holistic and transcultural vision that embraces the complexities of diasporic Christian life while fostering integration and broader societal engagement.